QoS Guarantee for Next Generation Network in the VoIP System - Hongjiao Peng; Shangdong Liu; Xiamei Chen (Dianxin kexue)
For the QoS of VoIP system, integrating the service based mechanism of network policy control within 3GPP IMS into QoS of VoIP, the SIP was adopted as signaling protocol. The function architecture with QoS capabilities and model of layered QoS control was proposed. Based on the investigation of QoS calling control process, a SIP delegate, feature requirement of UE and router with QoS information were introduced. The module armed with policy decision ability was created. The QoS interacting messages between interfaces of all modules were studied. Through utilizing the suggested mechanism in QoS modules and prototype of VoIP SIP-QoS delegating server, feasibility and availability were validated.